Anaerobic co-digestion of sewage sludge and slaughterhouse waste in existing wastewater digesters. (January 2020) - Salehiyoun, Ahmad Reza; Di Maria, Francesco; Sharifi, Mohammad; Norouzi, Omid; Zilouei, Hamid; Aghbashlo, Mortaza
Abstract: The effect of co-digesting slaughterhouse waste (SHW) with waste mixed sludge (WMS) for possible implementation in a full-scale digester in an existing wastewater treatment plant (WWTP) was investigated. Biomethane potential (BMP) runs were activated using SHW:WMS ratios from 0% to 60% at total solids (TS) of 4% and 7%. Higher values of BMP of about 735 NLCH4/kg volatile solids (VS) were obtained for the run with a SHW:WMS ratio of 40% and TS = 4%. Continuous runs were also performed using the same SHW:WMS ratio at different organic loading rates (OLR). The maximum biomethane generation of 550 NLCH4 /kgVS was achieved for an OLR = 1.5 kgVS/m 3 .day. Stability monitored by FOS/TAC showed values < 0.7 for OLR up to 2.0 kgVS/m 3 .day. The amount of SHW processable in the full-scale digester of the WWTP ranged from about 1.8 MgTS/day to 3.0 MgTS/day with a biomethane production of about 2300 Nm 3 /day and 1400 Nm 3 /day, respectively. Highlights: Co-digestion of SHW and WMS was investigated at different OLR. The BMP increased from 438.4 NLCH4 /kgVS to 736.4 NLCH4 /kgVS. For full scale digester 2320 Nm 3 CH4 /day can be produced at OLR = 1.5kgVS/m 3 .day. Amount of SHW for co-digestion in full scale digester up to 3.0 MgTS/day.